PkM, Inovasi Jajan Tradisional Begina di Desa Pesaban Kecamatan Rendang, Karangasem - Ida Ayu Elistyawati; Luh Linna Sagitarini; I Gusti Made Wendri; Ni Wayan Merda Surya Dewi (Jurnal Abdimas Multidisiplin, 2022)
Purpose: The training aims to empower women in the village of Pesaban, through empowerment, participating in training in making snacks like this was expected to be a solution in creating the economy. Creatively through the skills of the participants to make Snack Bagina with various improvements through the texture of taste and coloring so that it has aesthetic value and higher selling value. Method: This community service activity is varied out from May to June 2022. The activity is carried out by explaining training materials on food processing, practicing innovative snack processing and facilitating discussions between. Explaining training materials on food processing, practicing innovative snack processing and facilitating discussions between participants. Participants are evaluated through pre-test and post- test. Result: Community Service Activities/PKM Begina Traditional Snack innovation in Pesaban Village Rendang District, Karangasem can be said to be successful both. The results of discussions with participants and the results off evaluating the results off training from participants a total of 14 people re[resenting PKM actors and PKK women assessed the training. From the statements collected that most (100%) participants showed an increased desireto innovate in the processing of traditional snack like this Limitation: This training is to the skill of PKK d and IKM members iin nnovation in processing traditional snack. Contribution: This training fosters innovation in the processing of traditional snack like this in Pasaban Village, Rendang district so that they can compete in local and global market.